2017
DOI: 10.1016/j.bjane.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of sugammadex and neostigmine on postoperative nausea and vomiting

Abstract: At the end of our study comparing neostigmine with sugammadex for neuromuscular blockage antagonism, we found use of sugammadex had lower incidence of PONV in the postoperative 1st hour and less anti-emetic use in 24 hours of monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 24 publications
(32 reference statements)
2
25
3
Order By: Relevance
“…A meta‐analysis of 17 randomised trials involving 1553 patients reported that the relative risk of nausea after sugammadex was 0.94 (95%CI 0.79–1.13), and of vomiting 0.87 (95%CI 0.67–1.17 . Since this systematic review, several small studies have suggested that PONV may be transiently reduced in the first hour or so after reversal with sugammadex, although not subsequently . This positive finding is consistent with previous data but the quality of evidence is low, because all studies have been either retrospective cohort studies or small clinical trials with poor bias control such as inadequate blinding or power, or only positive findings for a secondary outcome.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…A meta‐analysis of 17 randomised trials involving 1553 patients reported that the relative risk of nausea after sugammadex was 0.94 (95%CI 0.79–1.13), and of vomiting 0.87 (95%CI 0.67–1.17 . Since this systematic review, several small studies have suggested that PONV may be transiently reduced in the first hour or so after reversal with sugammadex, although not subsequently . This positive finding is consistent with previous data but the quality of evidence is low, because all studies have been either retrospective cohort studies or small clinical trials with poor bias control such as inadequate blinding or power, or only positive findings for a secondary outcome.…”
Section: Introductionsupporting
confidence: 86%
“…Yagan et al conducted a randomised trial in a mixed surgical population, and found that those patients receiving sugammadex had a lower incidence of PONV in the first postoperative hour (but not across 24 h), and required less treatment on the first postoperative day. Their patient groups were not matched for PONV risk (which may have confounded the results) and the dose of neostigmine used was larger than in our study . Geldner et al reported no significant difference in PONV, but acknowledged that their randomised controlled trial was underpowered to evaluate this outcome .…”
Section: Discussionmentioning
confidence: 70%
“…Most unwanted effects were bradycardia, increased sputum, dry mouth, headache, nausea, and vomiting. The proportion of patients suffering from these unwanted effects was similar to other studies [23], [24]. There is still no evidence in the literature to blame headache and nausea for using sugammadex or neostigmine as well because there were many affected factors.…”
Section: Discussionsupporting
confidence: 83%
“…[7,21] An advantage of sugammadex for PONV has also been reported by several studies. [8,22,23] Cholinergic effects from the use of cholinesterase inhibitors can cause a decrease in oesophageal tone, and an increase in secretion and intestinal movement that might be associated with the increased PONV. However, due to the fear of these potential side effects, anticholinergic agents have been used to compensate for these unwanted cholinergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Besides the fast reversibility of NM blockade, advantageous effects of this agent on recovery components after anaesthesia such as consciousness, nausea/vomiting, or physiologic factors have been reported. [7][8][9] Nonetheless, controversial results on the superiority of sugammadex over conventional NM blockade reversal agents have been reported. [10,11] The Post-operative Quality Recovery Scale (PQRS) assesses the quality of postoperative recovery over time using six domains of recovery.…”
Section: Introductionmentioning
confidence: 99%